Optimization Metrics Model: The Mobile Wallet for Merchant Ecosystem. (June 2020) - Syah, R; Nasution, M K M; Nababan, E B; Efendi, S
Abstract: Finance Technology (FinTech) is a combination of financial services and technology that ultimately changes the business model. Appears as changes in people's lifestyles are currently dominated by users of fast-paced information technology. Financial technology provider which includes payment systems, market support, investment management, and risk management, loans, financing, and capital providers, and other financial services. North Sumatra has 33 municipal districts with an area of 72, 981.23 km2 and a population of 13, 937, 797 people, with a density of 191 people / km2. Each city district has various. Percentage of user demographics ranging from 0.07% to 66.9% spread in North Sumatera Province. This can be seen from each region having different interests and abilities. Each district has various merchants that are built on every corner or roadside sample of 1, 300 user data. LRM method to transaction types is divided into two with a merchant transaction frequency value of 263 and transaction biller 448.